To overhaul or revolutionise IPT? - Abd Razak, Dzulkifli (2009)
MALAYSIA is said to be trapped within a moderate economic level. This resulted from the failure of our public and private universities or the institutions of higher learning (IPT) to churn out graduates for a higher level economy as they are entangled in meeting the outdated job market. Much to our dismay, the market is not capable of or interested in making forays into the future. As a result, our job market is lagging far behind our competitors and that of the developed countries.